Creating a Sensation: “University is a Library” - Kenan Erzurum (Türk Kütüphaneciliği, 2013)
The provision of library services is a function of an institution’s outlook as well as its available resources. Likewise, the “university as a library” approach is related to an institution’s ability to satisfy library patrons by meeting user need.